Non-Pharmacological Pain Management in Elderly Patients Undergoing Hemodialysis at Prof. Dr. H. Aloei Saboe Regional Hospital, Gorontalo City - Gobel, Inne Ariane; Jole, Israwati Oktavia; Ilham, Rosmin (Jambura Nursing Journal, 2026)
Pain management in the elderly is a complex challenge, particulatly in a non-pharmacological context. This study aims to determine pain management in elderly patients undergoing hemodialysis at Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City. The design of this study uses a quantitative approach, using a descriptive method. The population in this study were patients undergoing hemodialysis related to Non-Pharmacological Pain Management in all elderly undergoing hemodialysis at Prof. Dr. H. Aloei Saboe Hospital with a total of 46. The sampling technique used purposive sampling with a total of 31 samples. The results of the study showed that with the title Non-Pharmacological Pain Management in Elderly Patients Undergoing Hemodialysis at Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City. H. Aloei Saboe Gorontalo City can be concluded that non-pharmacological pain management with the majority in the sufficient category amounted to 26 respondents (83.8%), the good category amounted to 3 respondents (9.7%) and the less category amounted to 2 (6.5%). The conclusion in this study of non-pharmacological pain management in the elderly is that most are in the sufficient category (83.8%), this study is expected to contribute to the development of more effective pain management strategies for the elderly